Differential Influence of Pueraria lobata Root Extract and Its Main Isoflavones on Ghrelin Levels in Alcohol-Treated Rats - Michał Szulc; Radosław Kujawski; Justyna Baraniak; Małgorzata Kania-Dobrowolska; Ewa Kamińska; Agnieszka Gryszczyńska; Kamila Czora-Poczwardowska; Hanna Winiarska; Przemysław Ł. Mikołajczak (Pharmaceuticals, 2021)
The study was carried out on alcohol-preferring male Wistar rats. The following drugs were repeatedly (28×) administered: acamprosate (500 mg/kg, p.o.), naltrexone (0.1 mg/kg, i.p), and Pueraria lobata (kudzu) root extract (KU) (500 mg/kg, p.o.) and its isoflavones: daidzin (40 mg/kg, p.o.) and puerarin (150 mg/kg, p.o.). Their effects on a voluntary alcohol intake were assessed. KU and alcohol were also given for 9 days in an experiment on alcohol tolerance development. Finally, total and active ghrelin levels in peripheral blood serum were measured by ELISA method. Acamprosate, naltrexone, daidzin, and puerarin, reducing the alcohol intake, caused an increase in both forms of ghrelin levels. On the contrary, though KU inhibited the alcohol intake and alcohol tolerance development, it reduced ghrelin levels in alcohol-preferring rats. The changes of ghrelin concentration could play a role as an indicator of the currently used drugs. The other effect on the KU-induced shift in ghrelin levels in the presence of alcohol requires further detailed study.